Efficacy of liquid biopsy for genetic mutations determination in non-small cell lung cancer: a systematic review on literatures - Mohammad Mehdi Jahani; Parisa Mashayekhi; Mir Davood Omrani; Azita Azimi Meibody (BMC Cancer)
Abstract Background Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related mortality worldwide and is often diagnosed at advanced stages, limiting treatment options. This systematic review aims to evaluate the efficacy of liquid biopsy in detecting genetic mutations in NSCLC, focusing on its sensitivity, specificity, clinical utility, and potential to guide personalized treatment strategies. Methods A systematic search was conducted in PubMed, Scopus, Embase, Web of Science, and Cochrane Library to identify relevant studies published between 1990 and September 2024. Eligible studies included comparative analyses of liquid biopsy techniques for NSCLC diagnosis, prognosis, progression, or treatment response. This review adheres to the PRISMA 2020 guidelines and assesses study quality using the QUADAS framework. Results A total of 30 studies were included. Digital droplet PCR (ddPCR) demonstrated the highest sensitivity, detecting low-frequency mutations such as EGFR T790M at levels as low as 0.01%. Next-generation sequencing (NGS) provided comprehensive mutational profiling, revealing tumor heterogeneity and co-existing mutations but required high-quality plasma samples. The cobas EGFR Mutation Test, while less sensitive than ddPCR, remains widely used due to its clinical accessibility. Emerging methods, including extracellular vesicle analysis, show promise but require further validation. Additionally, liquid biopsy effectively identified non-EGFR mutations, such as KRAS, ALK, and MET amplifications, expanding its clinical applicability. Conclusion Liquid biopsy is a transformative tool in NSCLC management, offering a minimally invasive approach for mutation detection, disease monitoring, and treatment guidance. Future research should focus on multicenter trials and emerging technologies to enhance clinical integration and broaden applicability across different cancer types.